Predicting Credit Card Frauds in India: An Empirical Investigation - Puri, Lokendra; Singh, Ranjit; Bhuyan, Rafiqul (International Journal of Economics and Financial Issues, 2024)
This study attempts to predict credit card fraud and to know the factors responsible for credit card fraud. Using primary data of 7,500 credit card holders, collected using a questionnaire, this study conducts statistical analysis using discriminant analysis method. It is observed that variables, such as distance from home, distance from the last transaction, ratio to the median purchase price, used chip, used PIN for the transaction, and online order are significant factors in contributing to credit card fraud.